STRATEGIC TRANSFORMATIONS: ASSESSING THE INTERPLAY OF DIGITAL COMMERCE, TRADITIONAL TRADE, AND EMERGING MARKET TRENDSIN THE GLOBAL BUSINESS LANDSCAPE - Alfiana Alfiana; Listiana Sri Mulatsih; Al-Amin; Muhamad Stiadi; Dede Gustian (ADISAM Publisher, 2023)
In this comprehensive study titled